ОБ АНТРОПОНИМАХ КАРАКАЛПАКОВ - Бекниязов, К. (SCIENCE and SOCIETY, 2022)
The article tells about the customs and rituals of naming, about the traditional motives of naming the name of the Karakalpaks, about the trends of its development at the present time.